Exploring the Gap Between Consumers’ Green Rhetoric and Purchasing Behaviour - Johnstone, Micael-Lee (Journal of business ethics, 2015)
Why do consumers who profess to be concerned about the environment choose not to buy greener products more regularly or even at all? This study explores how consumers’ perceptions towards green products, consumers and consumption practices (termed green perceptions) contribute to our understanding of the discrepancy between green attitudes and behaviour. This study identified several barriers to ethical consumption behaviour within a green consumption context. Three key themes emerged from the study, ‘it is too hard to be green’, ‘green stigma’ and ‘green reservations’. There is currently a perception, based on a number of factors, that it is too hard to be green, which creates a barrier to purchasing green products. Furthermore, some consumers were reluctant or resistant to participate in green consumption practices due to their unfavourable perceptions of green consumers and green messages. This article suggests that green perceptions may influence consumers’ intention to purchase green products. Accordingly, it discusses the implications, and suggests avenues for future research.